Residual ground glass opacities three months after Covid-19 pneumonia correlate to alteration of respiratory function: The post Covid M3 study. (August 2021) - Frija-Masson, Justine; Debray, Marie-Pierre; Boussouar, Samia; Khalil, Antoine; Bancal, Catherine; Motiejunaite, Justina; Galarza-Jimenez, Maria Alejandra; Benzaquen, Hélène; Penaud, Dominique; Laveneziana, Pierantonio; Malrin, Roxane; Redheuil, Alban; et al.
Abstract: Introduction: Lung function in survivors of SARS-Co-V2 pneumonia is poorly known, but concern over the possibility of sequelae exists. Methods: Retrospective study on survivors with confirmed infection and pneumonia on chest-CT. Correlations between PFT and residual radiologic anomalies at three months taking into account initial clinical and radiological severity and steroid use during acute phase. Results: 137 patients (69 men, median age 59 (Q1 50; Q3 68), BMI 27.5 kg/m 2 (25.1; 31.7)) were assessed. Only 32.9% had normal PFT, 75 had altered DLCO. Median (Q1; Q3) values were: VC 79 (66; 92) % pred, FEV1 81 (68; 89), TLC 78 (67; 85), DLCO 60 (44; 72), and KCO 89 (77; 105). Ground glass opacities (GGO) were present in 103 patients (75%), reticulations in 42 (30%), and fibrosis in 18 (13%). There were significantly lower FEV1 (p = 0.0089), FVC (p = 0.0010), TLC (p < 0.0001) and DLCO (p < 0.0001) for patients with GGO, lower TLC (p = 0.0913) and DLCO (p = 0.0181) between patients with reticulations and lower FVC (p = 0.0618), TLC (p = 0.0742) DLCO (p = 0.002) and KCO (p = 0.0114) between patients with fibrosis. Patients with initial ≥50% lung involvement had significantly lower FEV1 (p = 0.0019), FVC (p = 0.0033), TLC (p = 0.0028) and DLCO (p = 0.0003) compared to patients with ≤10%. There was no difference in PFT and residual CT lesions between patients who received steroids and those who did not. Conclusion: The majority of patients have altered PFT at three months, even in patients with mild initial disease, with significantly lower function in patients with residual CT lesions. Steroids do not seem to modify functional and radiological recovery. Long-term follow-up is needed. Highlights: Lung function impairment affects almost 70% of patients at three months after SARS-CoV-2 pneumonia, mostly diffusion capacity alteration. Residual ground glass opacities, reticulations or fibrosis are significantly correlated to lower DLCO at three months. Initial extensive pneumonia (at least 50% of parenchyma involvement) is associated with poorer lung function at three months (VC, FEV1, DLCO). In this retrospective study, steroids during acute phase had no effect on PFT values at three months.